Management of Solid Medical Waste at Regional Public Hospital of West Papua Province - Towansiba, Saulus; Martanto, Eko A.; Mangallo, Bertha (Jurnal Penelitian Pendidikan IPA, 2024)
This study aims to characterize, identify and evaluate the management of solid medical waste in the West Papua Province Regional Public Hospital. This  research  is  descriptive  qualitative  research  conducted  in  December 2023 -January  2024  at  the emergency room, obstetrics ward, pediatric ward, perinatology ward, surgical room, internal disease department and laboratory. The results research are the average amount of solid medical waste in West Papua Province Regional Public Hospital is 282.3 kg/month, consisting of infectious solid medical waste of 229 kg/month and the amount of infectious sharps medical waste of 53.3 kg/month. The process of solid medical waste management of hospitals in West Papua Province Regional Public Hospital has referred to the Government Regulation of the Republic of Indonesia Number 7 of 2019, although the results are not all appropriate.